2020
DOI: 10.1097/md.0000000000023087
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation therapy for patients with glioma

Abstract: Background: Glioma is the most common type of brain tumor because of the destructiveness of the disease itself and the side effects of treatment, patients often leave symptoms of neurological defects. At present, rehabilitation treatment is not popular in glioma patients. There is a lack of definite evidence to prove the benefits of rehabilitation therapy for glioma patients. The purpose of this meta-analysis is to determine whether rehabilitation therapy can significantly improve the prognosis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…More recently, a systematic review and meta-analysis evaluated the effectiveness of rehabilitation therapy for patients with glioma, including only papers (8) that used the Functional Independence Measure (FIM) as outcome measure, with a total of 375 patients. Meta-analysis of total FIM ( P < .001), motor FIM ( P < .001) and cognitive FIM ( P < .001) indicated that rehabilitative intervention induced a significant improvement of functional prognosis and QoL of glioma patients, through the recovery of motor and cognitive functions [34]. Similarly the beneficial effects of rehabilitation was confirmed by a focused review that underlined the need for an individualized multidisciplinary rehabilitation intervention to treat functional impairment due to the tumour itself and/or treatment-related dysfunction [30 ▪ ].…”
Section: Text Of Reviewmentioning
confidence: 99%
“…More recently, a systematic review and meta-analysis evaluated the effectiveness of rehabilitation therapy for patients with glioma, including only papers (8) that used the Functional Independence Measure (FIM) as outcome measure, with a total of 375 patients. Meta-analysis of total FIM ( P < .001), motor FIM ( P < .001) and cognitive FIM ( P < .001) indicated that rehabilitative intervention induced a significant improvement of functional prognosis and QoL of glioma patients, through the recovery of motor and cognitive functions [34]. Similarly the beneficial effects of rehabilitation was confirmed by a focused review that underlined the need for an individualized multidisciplinary rehabilitation intervention to treat functional impairment due to the tumour itself and/or treatment-related dysfunction [30 ▪ ].…”
Section: Text Of Reviewmentioning
confidence: 99%
“…Glioma patients have a wide range of palliative care requirements, including requirements for physical, psychological, social, and spiritual support. Rehabilitation plays a very crucial role in the prevention of postoperative complications after any neurosurgery, like deep vein thrombosis and pressure sores due to prolonged bed rest, reduces the length of hospital stay, decreases time on ventilation, improves muscle strength, and increases independence in activities of daily living to improve functional capacity and quality of life [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…After the operation, the rehabilitation should involve a tailored plan aimed at restoring muscle strength and joint function, enhancing mobility, and providing the patient with the confidence to live an active life [ 8 ]. The rehabilitative intervention has an enormous effect on the patient's motor function, perception, psychology, and quality of life [ 9 ]. The key objective of physical therapy is to enhance the patient's motor skills, muscle tone, mobility, perception of sensation, and self-reliance.…”
Section: Introductionmentioning
confidence: 99%